THE FUNCTIONING OF THE VOCABULARY FOR MARKING INACCURATE TIME PERIODS IN THE SPEAKERS OF THE LOWER SUPERDNIPRIAN REGION THE FUNCTIONING OF THE VOCABULARY FOR MARKING INACCURATE TIME PERIODS IN THE SPEAKERS OF THE LOWER SUPERDNIPRIAN REGION - Bilenko, Tetiana; Myroniuk, Lina (Philological Treatises, 2023)
Time phenomenon plays an extremely important role in reflecting language and cultural peculiarities of any nation. Time is an integral aspect of our world model, a characteristic of existence duration, and an important part of people's lives, especially in the modern world, where it is becoming a valuable resource. The language picture of certain territories encodes the value content of time in different ways. Its decoding reveals the worldview of a cultural society. Time, as a component of the world’s language picture, is endowed with properties inherent in human thinking and worldview. Awareness of time as an integral element of reality is a source of cultural coding. The temporal code of culture is represented through the names of time intervals, which are understood as cultural signs. Their study in the ethnolinguistic context helps to reveal national specificity and characterize the linguistic traditions of a particular ethnic area.Based on the material of the famous ethnographic work "The Dictionary of Nyzhnia Naddniprianshchyna. (The Lower Dnieper Ukraine) Dialects" by Viktor Antonovych Chabanenko, the article analyses lexemes denoting inaccurate time intervals, one of the informative layers of dialect vocabulary, which was formed on the basis of wide and comprehensive use of all resources of the national language and became its organic part. The present study is devoted to the elucidation of the semantics, structure, lexical and word-formation meaning of these linguistic means to denote time, as well as to the identification of their potential possibilities recorded in the dictionary. The disclosure of time awareness peculiarities by Ukrainian people and the identification of time units that constitute the specificity of the lexical system of the dialects in Nyzhnia Naddniprianshchyna clearly reflects the individual perception of the world by the speakers of a particular ethnolinguistic area.